Evoked potentials in the Atlantic cod following putatively innocuous and putatively noxious electrical stimulation: a minimally invasive approach - Ludvigsen, Stian; Stenklev, Niels Chr.; Johnsen, Helge K.; Laukli, Einar; Matre, Dagfinn; Aas-Hansen, Øyvind (Fish Physiology and Biochemistry, 2013)
Aspects of peripheral and central nociception have previously been studied through recording of somatosensory evoked potentials (SEPs) to putative noxious stimuli in specific brain regions in a few freshwater fish species. In the present study, we describe a novel, minimally invasive method for recording SEPs from the central nervous system of the Atlantic cod (Gadus morhua). Cutaneous electric stimulation of the tail in 15 fish elicited SEPs at all stimulus intensities (2, 5, 10 and 20 mA) with quantitative properties corresponding to stimulus intensity. In contrast to previous fish studies, the methodological approach used in Atlantic cod in the current study uncovered a number of additional responses that could originate from multiple brain regions. Several of these responses were specific to stimulation at the highest stimulus intensities, possibly representing qualitative differences in central processing between somatosensory and nociceptive stimuli.